Response of Permafrost Thermal State to Global Climatic Change in Urbanised Landscapes, Yakutsk, Russia - Viktor V. Kunitsky; Igor I. Syromyatnikov; Andrey V. Litovko (Land, 2022)
A study was undertaken to investigate the structure and condition of urban permafrost in the city of Yakutsk. The response of permafrost to recent climate change was assessed for a Shergin Shaft site in a cryogenic landscape. The results indicate that the thickness of the active layer which consists of anthropogenic soils experienced no change during the second half of the 20th century and the early 21st century. However, the thermal state of the underlying alluvial sediments has changed significantly in response to the warming of the climate. The permafrost temperatures at a depth of 10 m increased by about 3 °C between 1934 and 2015.